An Anxious Pursuit : Agricultural Innovation and Modernity in the Lower South, 1730-1815 - Chaplin, Joyce E. (Book collections on Project MUSE., 1993)
Indeed, whites continued to wonder whether their innovations, some of them defied by slaves, truly improved the region. Chaplin argues that these apprehensions prefigured the antimodern stance of the antebellum period, but she contends that they were as much a reflection of the doubt inherent in theories of progress as an outright rejection of those ideas.